Antioxidant activity and in-vitro antiproliferative effect of various solvent extracts of ficus carica fruit on breast cancer cell line (MCF-7) - Rufa'i Umar Zubair
Breast cancer is one of the commonest cancers with various biochemical therapeutic options but most of them are toxic to the body. Plants have been recognized as alternative sources of remedy for various ailments as they contain many phytochemical substances. This study was conducted to extract dried Ficus carica fruit using solvents of different polarity. The study aimed to determine the total phenolic contents, total flavonoid contents, antioxidant activity of all the extracts as well as to investigate their antiproliferative activity on breast cancer cell line (MCF-7) with mouse epithelial cell line (3T3) as a control. The Ficus carica fruit was extracted with three solvents i.e. ethanol (polar), ethyl acetate (semi polar) and hexane (non-polar). Total Phenolic Content (TPC) from all the extracts was estimated using Folin-Ciocalteu's reagent, while Total Flavonoid Content (TFC) was estimated using A1-Cl colorimetric method and both the results were compared to the standard curves accordingly. Determination of antioxidant was demonstrated by 2,2-diphenylpicryUlydrazyl (DPPH) scavenging assay while the antiproliferative activity of the extracts was determined using (3-(4,5-dimethylthiazol-2- yl)-2,5-diphenyltetrazolium bromide) ( MTT) assay. The correlation between the total phenolic, total Flavonoid and antioxidant activity as well as correlation between anti proliferative activity and antioxidant activity were also determined. The highest percentage of extract yield was obtained from ethanol solvent (18.72 %) compared to ethyl acetate (0.57 %) and hexane (0.48%) solvents. However the highest TPC (90.34±0.006 mg GAE/g extracts) and Total Flavonoid Contents (219±0.020 mg ofQEI g extracts) were obtained from ethyl acetate extracts followed by ethanol extract. The lowest TPC and TFC content was obtained from hexane extract. High antioxidant activity was demonstrated by ethyl acetate extract (ICso=580 ug/ml.), whereas ethanol and hexane extracts exhibit low antioxidant activity. A significant antiproliferative effect on breast cancer cell (MCF-7) was also demonstrated by ethyl acetate extract but not the ethanol and hexane extracts. Interestingly, no significant antiproliferative activity on mouse epithelial cell line was demonstrated by ethyl acetate extract. There was a positive correlation between TPC, TFC and antioxidant activity (r=.866, P<O.Ol). A negative correlation was also seen between the antioxidant activity and proliferative activity (r=.687 P<O.Ol). In conclusion the ethanol (polar) solvent showed the highest percentage extract yield compared to the ethyl acetate and hexane. However the highest TPC and TFC were obtained from ethyl acetate (semi polar) extract and this is positively correlated with its high antioxidant activity and antiproliferative activity against breast cancer cell (MCF-7). Therefore, these studies provide promising results on the chemotherapeutic potential of Ficus carica fruit extracts.